2018
DOI: 10.1038/s41431-017-0089-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of the chromosome 15q25.1 in COPD through epigenetics and transcriptomics

Abstract: Chronic obstructive pulmonary disease (COPD) is a major health burden in adults and cigarette smoking is considered the most important environmental risk factor of COPD. Chromosome 15q25.1 locus is associated with both COPD and smoking. Our study aims at understanding the mechanism underlying the association of chromosome 15q25.1 with COPD through epigenetic and transcriptional variation in a population-based setting. To assess if COPD-associated variants in 15q25.1 are methylation quantitative trait loci, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…In a collaborative GWAS we identified 82 genetic loci significantly associated with COPD, of which 14 were shared with asthma or pulmonary fibrosis, confirming our previous observations of overlap between COPD loci and loci for lung function and pulmonary fibrosis [335]. Through epigenetic and transcriptomic studies, we demonstrated that genetic variants at chromosome 15q25.1 (encompassing the nicotinic acetylcholine receptor 3 [CHRNA3] gene and the iron-responsive element binding protein 2 [IREB2] gene) are differentially methylated in blood and differentially expressed in lung tissue of COPD cases and controls [336]. Similarly, we have elucidated the relation of the top COPD GWAS variant at chromosome 19q13.2 with DNA methylation and gene expression in blood and lung tissue [337].…”
Section: Main Results In the Last 3 Yearssupporting
confidence: 87%
See 1 more Smart Citation
“…In a collaborative GWAS we identified 82 genetic loci significantly associated with COPD, of which 14 were shared with asthma or pulmonary fibrosis, confirming our previous observations of overlap between COPD loci and loci for lung function and pulmonary fibrosis [335]. Through epigenetic and transcriptomic studies, we demonstrated that genetic variants at chromosome 15q25.1 (encompassing the nicotinic acetylcholine receptor 3 [CHRNA3] gene and the iron-responsive element binding protein 2 [IREB2] gene) are differentially methylated in blood and differentially expressed in lung tissue of COPD cases and controls [336]. Similarly, we have elucidated the relation of the top COPD GWAS variant at chromosome 19q13.2 with DNA methylation and gene expression in blood and lung tissue [337].…”
Section: Main Results In the Last 3 Yearssupporting
confidence: 87%
“…An integrative cross-omics analysis of DNA methylation sites have identified multiple CpGs for T2D, glucose and insulin homeostasis, and further showed the differential methylation explains at least 16.9% of the association between obesity and insulin [96]. Multi-omics analysis using the Rotterdam Study epigenetics and transcriptomics data also showed that regulatory mechanisms affecting the expression of IREB2 gene, such as DNA methylation, may explain the association between genetic variants in chromosome 15q25.1 and COPD, largely independent of smoking [336]. Likewise, a systematic analysis integrating GWAS, gene expression and DNA methylation data indicated multiple long non-coding RNAs associated with cardiometabolic disorders [358].…”
Section: Integrative Omics and Systems Epidemiologymentioning
confidence: 98%
“…24 COPD and lung cancer-associated variants in 15q25 are known expression and methylation QTL (eQTL and meQTL) for multiple genes and tissues. 3,25 It has not been possible so far to definitely identify all of the causal gene(s) at this locus, but most evidence points toward CHRNA5 (cholinergic receptor nicotinic alpha 5 subunit) or IREB2 (iron-responsive element binding protein 2). In our study, we focused specifically on gene expression in lung tissues with the hope to identify genes directly involved in lung cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated whether MIF, DDT and DDTL expression levels were influenced by the presence of SNPs. To this end, we performed a cis-eQTL analysis 19 for these three genes using the entire lung tissue dataset (n = 1087), which contains mostly patients with COPD with or without lung cancer, lung cancer patients with normal lung function (Non-COPD controls), and a few patients with a variety of interstitial lung diseases. A schematic representation of the step-by-step approach for the eQTL, subsequent analyses and the main results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here cis-eQTL is defined as the SNPs significantly associated with gene expression and located within 1 Mb from either side of the binding side of the probe. The eQTL analysis was performed using the lung tissue dataset, as described previously 19 . Briefly, the association between SNPs and the 2-log transformed gene expression of MIF, DDT and DDTL was tested in each cohort (Laval, British Columbia and Groningen).…”
Section: Gene Expression Analysismentioning
confidence: 99%